Black Brant Branta bernicla nigricans forage at both tides on Humboldt Bay, California, USA - Elkinton, Elizabeth; Lo, Long; Black, Jeffrey M. (Wildfowl, 2013)
Black Brant Branta bernicla nigricans arrive at their breeding grounds in arctic and subarctic North America and eastern Russia in spring, a time when food resources are limited. They rely largely on energy stores, acquired at staging sites, for migration and to support egg laying and incubation. In California, Humboldt Bay is the most important staging site for Black Brant due to the abundance of Common Eelgrass Zostera marina along its shores. Access to Common Eelgrass has been assumed to be limited to low tides, when the plants are reachable, and that little feeding occurs at higher tides. We tested this assumption by quantifying Black Brant foraging behaviour throughout the tidal cycle, including in relation to factors that contribute to the occurrence of detached Common Eelgrass leaves, which float to the surface and thus become available to the birds at higher tides. Throughout the winter and spring periods (January–April 2011) Black Brant at Humboldt Bay foraged directly on Common Eelgrass beds during low tides and continued to feed on drifting leaves during higher tides. They switched from bed-feeding to drift-feeding at a mean tide height of 0.9 m. On average, 48% of flock members typically fed when Common Eelgrass beds were reachable during low tides, with 24% of birds feeding on drifting eelgrass during higher tides. The prevalence of drift-feeding declined as the tide level increased in the bay, ranging from 35% of birds at 1 m tides to 10% at 2.5 m tides. The amount of drifting Common Eelgrass available to Black Brant increased with higher maximum wind speeds and greater tidal range in the previous 24 h, and with greater numbers of Black Brant on the bay. By providing current information about foraging strategies and the use of high-tide feeding opportunities, this study can inform future projections of the carrying capacity of Humboldt Bay for staging Brant. This is particularly important in light of projected future impacts of sea level rises on food availability at staging habitats along the Pacific Flyway.